A influência de personagens na preferência por alimentos saudáveis na infância: um estudo com base na equivalência de estímulos - Paes, Stéfanie Hansen (2023)
The field of attitude studies allows us to investigate how prior experience influences an individual's responses to objects and situations they engage with. This concept can also be used to understand the choice and preference for specific products or foods, using the stimulus equivalence paradigm. Thus, the aim of the present study was to determine if children's food preferences could be altered through the transfer of function, using the matching-to-sample method established between a healthy food item and a significant stimulus, in this case, their favorite character. Five preschool children underwent the experimental procedure, which included pre-test data collection with their daycare and caregivers to assess their food preferences and choices before the intervention. It also involved pre-training phases, relational training, and symmetry and transitivity testing. The results indicate that all participants formed equivalence classes containing their favorite character and their least preferred fruit. However, there was no change in food preference assessment after the pairing, which may be related to procedure variables (such as the nodal distance between stimuli) or the strength of pre-experimental relationships, contributing to the literature in the field of attitudes.